Implementation of Strategic Management in Learning to Improve Intisab Pui-Based Life Skills for Students (Case Study at Madrasah Aliyah Daarul Uluum Pui Majalengka) - Rahmatullah, Irfan; Hidayat, Wahyu (Journal of English Language and Education, 2026)
This study examines the implementation of strategic management in learning to improve life skills based on Intisab PUI in students at Madrasah Aliyah Daarul Uluum PUI Majalengka. The modern era demands that Islamic educational institutions be able to integrate spiritual values with practical skills, but there is still a gap in the implementation of effective strategies to achieve that balance. Therefore, this study aims to analyze the formulation, implementation, and evaluation of Intisab PUI-based learning strategies, as well as assess its effectiveness in improving students' life skills. The research uses a qualitative approach with a case study method. Data was obtained through in-depth interviews with madrasah heads, teachers, and students, observation of the learning process, and analysis of curriculum documents. The validity of the data is guaranteed through triangulation techniques. The results of the study showed that the formulation of the strategy resulted in the concept of "funny students" with a long-term plan for six years that integrated the values of the PUI Intisab into all subjects through SWOT analysis. The implementation of the strategy runs effectively through excellent programs, such as memorization of the Qur'an with a target of two juz, the development of multidimensional digital skills, project-based learning, and gradual spiritual coaching. The evaluation showed significant success, characterized by increased commitment of graduates to PUI scores, positive behavior changes, increased academic achievement, and mastery of technology and vocational skills. The findings of the study indicate that Intisab PUI-based learning strategic management is able to create a balance between religious, academic, and vocational aspects, and is effective in improving students' life skills. This model has the potential to be adapted by other madrasas in optimizing the development of life skills based on Islamic values in the modern era.